Huffazh Center Indonesia: Study and Development of Tahfidz Al-Qur'an at the Beginning of the 21st Century - Ikmal Mulia Harahap (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research uses a social history method with a qualitative research type to determine the role and development of the Huffazh Center Indonesia (HCI) in forming a generation of quality hafiz and hafizah amidst the dynamics of Islamic education in the 21st century. In the context of the 21st century, the importance of Al-Qur'an education in shaping the character and morals of Muslims is increasingly recognized, and evolutionary trends in Islamic education, especially memorizing the Koran, have become the main focus of this research. This article will provide a significant contribution to thinking and discussion regarding the future of Islamic education in Indonesia, by providing in-depth insight into the role of HCI in forming a quality generation and overcoming the educational and social challenges faced. Holistic approach, flexible curriculum and transparent fund management at HCI emphasizes the importance of tahfidz Al-Qur'an education as a means of maintaining religious and moral values and meeting the spiritual needs of society in facing changing times.